Exploring the Impact of Effective Internal Communication Strategies on Employee Morale, Productivity, and Organizational Culture - Joshua Kayode Okunade (Britain International for Academic Research (BIAR-Publisher), 2025)
This exploratory investigation examines the complex interplay between internal communication strategies and their ramifications on employee morale, productivity, and organizational culture, particularly within the domain of Public Relations (PR). In the realm of contemporary organizational management, internal communication strategies play a pivotal role in enhancing employee engagement, morale, productivity, and in shaping the organizational culture. This research delves into the effects of these strategies within a private university situated in Lagos, Nigeria. The facilitation of effective internal communication cultivates employee engagement, fortifies morale, and aligns organizational objectives, consequently leading to enhanced productivity. Nevertheless, numerous organizations encounter challenges in the proficient implementation of these strategies. The study accentuates the importance of strategic, ethical, and leadership-oriented communication practices in nurturing a positive organizational culture, which ultimately contributes to the overarching success of the organization. This paper investigates the strategic significance of internal communication in amplifying employee engagement, morale, productivity, and in molding organizational culture. Utilizing Social Identity Theory and Organizational Identification as a theoretical framework, the study scrutinizes how communication strategies engender a sense of belonging among employees, which favourably influences their attitudes and behaviours. The research, conducted at a private university in Lagos, Nigeria, through comprehensive interviews with seven employees encompassing both non-teaching and academic staff, reveals a disconnection between internal communication practices and employee engagement, thereby underscoring the necessity for more inclusive and transparent communication methodologies.